Giants in the Landscape : Monumentality and Territories in the European Neolithic : Proceedings of the XVII UISPP World Congress (1–7 September, Burgos, Spain): Volume 3 / Session A25d /: Monumentality and Territories in the European Neolithic : Proceedings of the XVII UISPP World Congress (1–7 September, Burgos, Spain): Volume 3 / Session A25d. (2016) - Unknown
No abstract available